AN EXPERIMENTAL STUDY OF ENSTATITE DISSOLUTION RATES AS A FUNCTION OF PH, TEMPERATURE, AND AQUEOUS MG AND SI CONCENTRATION, AND THE MECHANISM OF PYROXENE/PYROXENOID DISSOLUTION - Oelkers E.H.; Schott J. (My University, 2001)
Steady state enstatite dissolution rates, at far from equilibrium conditions, were measured as a function of aqueous magnesium and silica activity, pH from 1 to 11, and temperature from 28°C to 168°C. All rates were measured in mixed flow reactors and exhibited stoichiometric dissolution. Rates at pH = 2 are independent of aqueous silica activity, but decrease with increasing aqueous magnesium activity; constant temperature rates decrease continuously with increasing pH over the whole investigated pH range. All measured rates can be described within experimental uncertainty using r = AA exp (-EA/RT)(aH+2/aMg2+)1/8where r signifies the enstatite steady state dissolution rate, AA refers to a pre-exponential factor equal to 2.4 x 10-4 (mol of enstatite)/cm2/s, EA designates an activation energy equal to 48.5 kJ/mol, R represents the gas constant, and T denotes absolute temperature.The variation of these rates with solution composition is interpreted to originate from the enstatite dissolution mechanism. The enstatite structure consists of silica tetrahedra chains that are branched together by magnesium octahedra. Mg-O bonds apparently break more rapidly than Si-O bonds in this structure. The breaking of Mg-O bonds, however, does not destroy the enstatite structure; it only partially liberates the silica tetrahedral chains by removing adjoining Mg atoms. Enstatite dissolution proceeds via (1) magnesium releasing exchange reactions between two aqueous H+ and Mg in the enstatite structure, followed by (2) the relatively slow detachment of silica from partially liberated tetrahedral chains. The rate is proportional to the concentration of partially detached Si tetrahedra on the enstatite surface, which is linked through the law of mass action for the Mg/proton exchange reaction to aqueous magnesium activity and pH. Due to their similar structure and reaction rate dependencies on solution composition, it is postulated that the pyroxene/pyroxenoid minerals exhibit similar dissolution mechanisms to that proposed for enstatite.